Proceedings of the Thirty-Second International Joint Conference on Artificial Intelligence 2023
DOI: 10.24963/ijcai.2023/298
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison of Multiwinner Voting Rules on Approval Elections

Abstract: In this paper, we experimentally compare major approval based multiwinner voting rules. To this end, we define a measure of similarity between two equal sized committees subject to a given election. Using synthetic elections coming from several distributions, we analyze how similar are the committees provided by prominent voting rules. Our results can be visualized as maps of voting rules, which provide a counterpoint to a purely axiomatic classification of voting rules. The strength of our proposed method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…In Table 1, we show the similarity between voting rules in terms of the average overlap of their computed committees. We observe a high consensus of all rules, thereby confirming previous findings on synthetic data (Reichert and Elkind 2023;Faliszewski et al 2023b); in fact, across all elections, two rules never disagree on more than 51 out of the k = 300 candidates. However, there are some differences: The four considered proportional rules have a particularly high agreement.…”
Section: A First View On Instances and Committeessupporting
confidence: 90%
See 2 more Smart Citations
“…In Table 1, we show the similarity between voting rules in terms of the average overlap of their computed committees. We observe a high consensus of all rules, thereby confirming previous findings on synthetic data (Reichert and Elkind 2023;Faliszewski et al 2023b); in fact, across all elections, two rules never disagree on more than 51 out of the k = 300 candidates. However, there are some differences: The four considered proportional rules have a particularly high agreement.…”
Section: A First View On Instances and Committeessupporting
confidence: 90%
“…Formally capturing proportional representation in the form of axioms, and designing rules that are guaranteed to satisfy these axioms, is a very active area of research; see the book by Lackner and Skowron (2022). While this effort has resulted in a good theoretical understanding of the axiomatic aspects of different voting rules, there are only very few studies that examine the actual behavior of such rules on specific real-world or synthetically generated voting instances (Elkind et al 2017;Szufa et al 2022;Faliszewski et al 2023b;Mehra, Sreenivas, and Larson 2023). Nevertheless, these few empirical works have already proved useful, as they found that different voting rules often produce similar outcomes and that most voting rules tend to significantly outperform their worst-case proportionality guarantees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation